Meu processo formativo: narrativas e reflexões de uma futura educadora - PINHEIRO, Luciane Gonçalves (2020)
The present Memorial deals with my formative process from basic education to graduation in the pedagogy course, identifying throughout this process the moment occurred to the choice by the teaching profession. This memorial constitutes a reflective narrative of my educational process, highlighting the moments that were recorded in memory in a positive way or not. Taking as a starting point the process of construction of reading and writing in elementary school, following with the considerations about high school through graduation, highlighting the perspectives coming from the theoretical knowledge about education and the art of teaching. I conclude by making a brief reservation on what has been presented, and set out my pretensions for the future as a teacher